Bony lesions in early tetrapods and the evolution of mineralized tissue repair. Issue 4 (27th September 2019) - Herbst, Eva C.; Doube, Michael; Smithson, Timothy R.; Clack, Jennifer A.; Hutchinson, John R.
Abstract: Bone healing is an important survival mechanism, allowing vertebrates to recover from injury and disease. Here we describe newly recognized paleopathologies in the hindlimbs of the early tetrapods Crassigyrinus scoticus and Eoherpeton watsoni from the early Carboniferous of Cowdenbeath, Scotland. These pathologies are among the oldest known instances of bone healing in tetrapod limb bones in the fossil record (about 325 Ma). X-ray microtomographic imaging of the internal bone structure of these lesions shows that they are characterized by a mass of trabecular bone separated from the shaft's trabeculae by a layer of cortical bone. We frame these paleopathologies in an evolutionary context, including additional data on bone healing and its pathways across extinct and extant sarcopterygians. These data allowed us to synthesize information on cell-mediated repair of bone and other mineralized tissues in all vertebrates, to reconstruct the evolutionary history of skeletal tissue repair mechanisms. We conclude that bone healing is ancestral for sarcopterygians. Furthermore, other mineralized tissues (aspidin and dentine) were also capable of healing and remodeling early in vertebrate evolution, suggesting that these repair mechanisms are synapomorphies of vertebrate mineralized tissues. The evidence for remodeling and healing in all of these tissues appears concurrently, so in addition to healing, these early vertebrates had the capacity to restore structure and strength by remodeling their skeletons. Healing appears to be an inherent property of these mineralized tissues, and its linkage to their remodeling capacity has previously been underappreciated.